Explaining the theory of the intrinsic relationship between the soul and the body with a critique of the theories of Ibn Sina and Mulla Sadra - mohammad daneshnahad; mohammadHASAN VAKILI; HAMED ZARPOYAN (حکمت اسرا, 2021)
So far, various theories have been proposed by the scholars about the relationship between the soul and the body, so that some, such as Ibn Sina, consider such a relationship based on the originality of transcendental nature and of the type of rider and composite, while others, such as Mulla Sadra, consider it based on the originality of existence. And the theory of the physicality of occurrence considers the soul to be inherent. This research is based on the method of information analysis and comparison of opinions in order to explain the inaccuracy or indefensibility of both theories and then to explain the theory of the intrinsic relationship between the soul and the body that has fundamental differences with Mulla Sadra's theory. On this basis, first Ibn Sina's theory on the relationship between the soul and the body and its defects is stated. To take. For a deeper critique of Mulla Sadra's theory, some of Mulla Sadra's arguments on the occurrence of the soul are also analyzed to examine the ineffectiveness of these arguments in proving the occurrence of the soul and the consequent inherent relationship between the soul and the body that Mulla Sadra seeks. In the third step, the theory of the intrinsic relationship between the soul and the body, which is different from Mulla Sadra's theory, is discussed in detail in four sections, and its differences with the theory of Ibn Sina and Mulla Sadra are explained.